Monitoring the Changes in Certain Hematological and Biochemical Parameters in Camels (Camelus Dromedaries) during Postpartum Period - El-Zahar, Heba; Zaher, H.; Alkablawy, A.; Sharifi S, Al; Swelum, A. (Journal of Fertility Biomarkers, 2017)
The postpartum period in camel are considered the most critical period for camel's health and for future fertility. The objective of the present study was to compare the clinical examination results and the concentration of hemoglobin, total protein, calcium and progesterone at different instances (1st, 3rd and 9th days) postpartum. Fifteen female camels during the postpartum period (1st, 3rd and 9th days) were included in the present study. Hematological, biochemical profiles and ultrasonographic examination were performed. The clinical examination results were normal and no evidence of clinical disease. The results of the hematological and biochemical findings were within the reference range obtained previously by our research team. The concentrations of hemoglobin, total protein, calcium and progesterone were measured at the 1st, 3rd and 9th days postpartum. Hemoglobin concentration differs significantly in the 3rd day (p=0.012) compared to the 1st day postpartum. Total protein showed significant increase in the 3rd day (p=0.003) compared to the 1st day postpartum. Calcium concentration showed significant increase in the 9th day (p=0.002) compared to the 1st and the 3rd days postpartum. Progesterone concentration showed significant decrease in the 9th day (p=0.004) compared to the 1st and the 3rd days postpartum. The ultrasonographic imaging of the uterus and ovaries showed normal uterine involution and no abnormal secretions in the uterus. It is concluded that, clinical examination, hematological and biochemical profiles are very important tools for monitoring female camels during postpartum period.
Keywords: camel; postpartum; progesterone; calcium and total proteins